Complete mitochondrial genomes and nuclear ribosomal RNA operons of two species of Diplostomum (Platyhelminthes: Trematoda): a molecular resource for taxonomy and molecular epidemiology of important fish pathogens - Brabec, Jan; Kostadinova, Aneta; Scholz, Tomáš; Littlewood, D Timothy J (Parasites & vectors, 2015)
BACKGROUND: The genus Diplostomum (Platyhelminthes: Trematoda: Diplostomidae) is a diverse group of freshwater parasites with complex life-cycles and global distribution. The larval stages are important pathogens causing eye fluke disease implicated in substantial impacts on natural fish populations and losses in aquaculture. However, the problematic species delimitation and difficulties in the identification of larval stages hamper the assessment of the distributional and host ranges of Diplostomum spp. and their transmission ecology. METHODS: Total genomic DNA was isolated from adult worms and shotgun sequenced using Illumina MiSeq technology. Mitochondrial (mt) genomes and nuclear ribosomal RNA (rRNA) operons were assembled using established bioinformatic tools and fully annotated. Mt protein-coding genes and nuclear rRNA genes were subjected to phylogenetic analysis by maximum likelihood and the resulting topologies compared. RESULTS: We characterised novel complete mt genomes and nuclear rRNA operons of two closely related species, Diplostomum spathaceum and D. pseudospathaceum. Comparative mt genome assessment revealed that the cox1 gene and its 'barcode' region used for molecular identification are the most conserved regions; instead, nad4 and nad5 genes were identified as most promising molecular diagnostic markers. Using the novel data, we provide the first genome wide estimation of the phylogenetic relationships of the order Diplostomida, one of the two fundamental lineages of the Digenea. Analyses of the mitogenomic data invariably recovered the Diplostomidae as a sister lineage of the order Plagiorchiida rather than as a basal lineage of the Diplostomida as inferred in rDNA phylogenies; this was concordant with the mt gene order of Diplostomum spp. exhibiting closer match to the conserved gene order of the Plagiorchiida. CONCLUSIONS: Complete sequences of the mt genome and rRNA operon of two species of Diplostomum provide a valuable resource for novel genetic markers for species delineation and large-scale molecular epidemiology and disease ecology studies based on the most accessible life-cycle stages of eye flukes.
Keywords: Male; Fish Diseases; cestodózy; fylogeneze; Platyhelminths; Phylogeny; operon; RNA helmintů; mužské pohlaví; RNA, Helminth; RNA, Ribosomal; ryby; genom mitochondriální; Fishes; Genome, Mitochondrial; Animals; Genome, Helminth; genom u helmintů; ženské pohlaví; RNA ribozomální; zvířata; nemoci ryb; ploštěnci; Female; Cestode Infections; Operon